2021
DOI: 10.3390/ijerph18126256
|View full text |Cite
|
Sign up to set email alerts
|

Pb Content, Risk Level and Primary-Source Apportionment in Wheat and Rice Grains in the Lihe River Watershed, Taihu Region, Eastern China

Abstract: This study detailed a complete research from Lead (Pb) content level to ecological and health risk to direct- and primary-sources apportionment arising from wheat and rice grains, in the Lihe River Watershed of the Taihu region, East China. Ecological and health risk assessment were based on the pollution index and US Environmental Protection Agency (EPA) health risk assessment model. A three-stage quantitative analysis program based on Pb isotope analysis to determine the relative contributions of primary sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, Cu is an essential oligo element that has been used in agriculture as fungicides and bactericides to protect plants (La Torre et al, 2018 ). Furthermore, a recent study demonstrated that fertilizer (nitrogen, potash, and organic) contributes to adding Pb in agricultural soils (Chen et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Cu is an essential oligo element that has been used in agriculture as fungicides and bactericides to protect plants (La Torre et al, 2018 ). Furthermore, a recent study demonstrated that fertilizer (nitrogen, potash, and organic) contributes to adding Pb in agricultural soils (Chen et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the indiscriminate use of agrochemicals, such as pesticides, fertilizers, and insecticides, and the use of sewage sludge and untreated industrial wastewaters make this problem worse [43]. Increasing evidence shows that the cultivation of crops on contaminated land can potentially result in the transfer of Pb from soil to the edible part of a crop [42,44,45]. This condition may also threaten the health of animals and human beings through the food chain.…”
Section: Status Of Lead In Plantsmentioning
confidence: 99%